Association between FGA gene polymorphisms and coronary artery lesion in Kawasaki disease - Liu, Xingzhu; Chen, Yanfei; Yang, Yanfei; Su, Zhongjian; Wang, Feng; Zhanghuang, Chenghao; Wu, Yuqin; Zhang, Xing (Frontiers in Medicine, 2023)
Objective To investigate the correlation between FGA gene polymorphisms and coronary artery lesion in Kawasaki disease. Methods Two hundred and thirty four children with Kawasaki disease (KD group), 200 healthy children (normal group) and 208 children with non-KD fever (fever group) were enrolled. General clinical indicators, the concentration of serum MMPs, TIMP-1, FG-α,fibrinogen level, molecular function (FMPV/ODmax) and FGA Thr312Ala polymorphism were detected individually by testing peripheral venous blood after fasting in the morning. Results There was no significant difference in average age among the three groups, which were 3.03 ± 1.22 years, 3.17 ± 1.30 years, and 3.21 ± 1.31 years, respectively. Compared with those in the fever group, the levels of white blood cell count (WBC), platelet count (PLT), procalcitonin (PCT), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), and fibrinogen (Fg) levels were significantly increased in the KD group. Red blood cell count (RBC) and hemoglobin (Hb) levels were significantly decreased (p < 0.05).The concentration of serum MMPs, TIMP-1, and FG-α in the KD and fever groups were significantly higher than those in the normal group (p < 0.05). The concentration of MMP-2, MMP-3, MMP-9, MMP-13, TIMP-1, and FG-α in the KD group were significantly higher than those in the fever group (p < 0.05).The KD group was divided into two subgroups,55 patients with combined CAL and 179 patients without combined CAL. The plasma fibrinogen concentration in the combined CAL group was significantly higher than that in the non-combined CAL and normal groups (p < 0.01). There was no statistically significant difference in FMPV/ODmax among the three groups (p > 0.05). Compared with normal group, the FGA GG, GA, and AA genotype and G, A allele frequency of the FGA gene polymorphism in the KD group showed no significant difference (p > 0.05). In the KD group, the most common type in children with CAL was GA, while the most common type in children without CAL was GG. Conclusion MMPs and FG-α were significantly upregulated in KD patients. The proportion of FGA genotype GA in children with CAL was significantly higher than that in children without CAL, suggesting that FGA gene polymorphisms affect coronary artery lesion in children with KD.